Takhrij and Syarah Hadith of Chemistry: Prohibition of Consuming Khamr in Science Perspective - Muhamad Farhan; Lisa Istianah; Muhlas Muhlas; Ali Masrur; Gina Giftia Azmiana Delilah (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad ï·º about the illegality of khamr. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this study are about the dangers of consuming khamr because it contains chemicals that can be intoxicating and damaging to human health. The conclusion of this study is takhrij and syarah hadith of the Prophet Muhammad ï·º concerning the prohibition of consuming khamr and staying away from it in order to save lives which is an inevitability. This study recommends the development of food technology science regarding harmful content in khamr through the field of chemistry.